A comparative study of National Family Health Survey-4 and National Family Health Survey-5 on quality of family planning services and unmet need for family planning indicators in Assam - Habib, Ashfia; Sharma, Sthapana; Saeed, Aamir; Bhaisya, Achyut C.; Ojah, Jutika (International Journal Of Community Medicine And Public Health, 2025)
Family planning is an important component of health, welfare, family stability as well as the social and economic progress of a community. The purpose of this study is to assess the shifts in the quality of family planning services and unmet needs in Assam based on National Family Health Survey (NFHS) rounds 4 and 5. The study is based on both NFHS-4 (2015-2016) and NFHS-5 (2019-2021) data and compares the major indicators; unmet need for family planning and quality of family planning services. Data disaggregated to district level were considered including total unmet need, demand for spacing, and the communication between health workers and female non-users regarding contraceptives. The current study shows that the overall total unmet need for family planning has declined in most of the districts in Assam when compared. However, when comparing districts large disparities have been found for certain districts demonstrating higher levels of unmet need. Contrary to this, the study established that the quality of family planning services measured by health worker’s interaction with non-users had increased in most districts but was still inadequate in the state. It is clear from the analysis that there has been significant improvement in family planning services, however; there are challenges concerning the use and availability of family planning services. Interventions proposed are strengthening interventions for certain groups, improving access, and increasing cultural competence.